CHARACTERISTIC LIGNOCELLULOSE OF SAGO SOLID WASTE FOR BIOGAS PRODUCTION - Hammado, Nururrahmah -; Utomo, Sudarno -; Budiyono, Budiyono - (Journal of Applied Engineering Science, 2020)
Biogas is an alternative energy that can be produced from various biomass, sago solid waste is one of them. Sago solid waste was obtained from processing sago stems into sago starch. Sago solid waste should be treated to separate lignocellulose that can be used as raw material for biogas production. In this study, pre-treatment was done to anaerobic fermentation. Physical pre-treatment was done by milling the biomass into small pieces. Chemical pre-treatment was done by using NaOH solvent, and biological pre-treatment used a microbial consortium. Characterization of pretreated sago solid waste was analyzed with Scanning Electron Microscopy (SEM) combined with Energy Dispersive X-Ray (EDX) for inorganic element composition analysis. The functional group changes were characterized by Fourier Transform Infrared (FTIR) and lignocellulosic composition was analyzed by the Van Soest method. The analysis of results showed that chemical and biological pretreatment significantly degradation lignocellulose than other methods based on morphologies of sago hampas granules. The biological pre-treatment was capable of degraded lignin up to 3.47% and hemicellulose 8.01%.